2022
DOI: 10.1245/s10434-022-12399-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA is Unreliable to Detect Somatic Gene Alterations in Gastrointestinal Peritoneal Carcinomatosis

Abstract: Introduction Tumor agnostic circulating tumor DNA (ctDNA) is routinely used to guide treatment decisions in gastrointestinal (GI) cancers, especially metastatic cancers. The amount of ctDNA detected in plasma is affected by stage, tumor burden, and tumor vascularization. We hypothesized that peritoneal carcinomatosis (PC) is associated with lower ctDNA levels than other metastatic sites in GI cancers due to the plasma–peritoneal barrier. Methods We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Our study of 279 patients with stages 2-4 GI malignancies found that the amount of plasma ctDNA is significantly lower in GI malignancies with PC than in visceral metastases. 6 The significance of this observation is further enhanced by the fact that the majority of the patients in this study had large volume of peritoneal disease burden, with an average of six intrabdominal regions involved. We also found that plasma ctDNA next-generation sequencing (NGS) showed fewer genomic alterations in patients with GI PC than tissue analysis, with a concordance rate of merely 18%.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Our study of 279 patients with stages 2-4 GI malignancies found that the amount of plasma ctDNA is significantly lower in GI malignancies with PC than in visceral metastases. 6 The significance of this observation is further enhanced by the fact that the majority of the patients in this study had large volume of peritoneal disease burden, with an average of six intrabdominal regions involved. We also found that plasma ctDNA next-generation sequencing (NGS) showed fewer genomic alterations in patients with GI PC than tissue analysis, with a concordance rate of merely 18%.…”
mentioning
confidence: 75%
“…We also found that plasma ctDNA next-generation sequencing (NGS) showed fewer genomic alterations in patients with GI PC than tissue analysis, with a concordance rate of merely 18%. 6 These observations underscore the important biologic differences in the shedding and transport of ctDNA between PC and visceral metastasis. Detection of ctDNA is affected by the anatomy of the peritoneum and peritoneal fluid transport, as well as by the histology of tumors that have a predilection to metastasize to the peritoneum.…”
mentioning
confidence: 88%
“…Firstgeneration liquid biopsies utilizing cell-free circulating tumor DNA (ctDNA) have shown promise in identification of molecular-residual disease (MRD), somatic gene alterations, and to assess treatment response in CRC; however, there are significant limitations. Specifically, ctDNA has poor sensitivity in mucinous cancers 5 and peritoneal carcinomatosis (PC), 6 with ctDNA detected in only 38-53% of patients with PC. 7,8 We recently reported that ctDNA is detected at significantly lower levels in PC compared with visceral metastasis (VM) and is unreliable to detect somatic gene alterations in gastrointestinal PC.…”
mentioning
confidence: 99%
“…7,8 We recently reported that ctDNA is detected at significantly lower levels in PC compared with visceral metastasis (VM) and is unreliable to detect somatic gene alterations in gastrointestinal PC. 6 Due to its dismal prognosis and the only site of disease in 44% of patients with CRC recurrence, 9 there is an urgent need to identify novel blood-based biomarkers that can accurately identify colon cancer regardless of tumor type and metastasis location.…”
mentioning
confidence: 99%
“…A major criticism of previous trials using oxaliplatin for perfusion was the inability to initiate or delay adjuvant chemotherapy after complications secondary to HIPEC. In the HIPECT4 trial, 70.8% of patients received adjuvant chemotherapy within 12 weeks of resection and HIPEC and 68.4% received resection alone; these percentages were even higher when the patients who had pT3N0 disease on final pathology were excluded.…”
mentioning
confidence: 99%